User Experience Evaluation on Production Performance Monitoring System Using Honeycomb Method - Moh. Sofyan Sauri; Arie Hidaya Putra; Emny Harna Yossy (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
In the era of digitalization in industries, companies are implementing the Digital Factory Operating System in various aspects, including monitoring production performance on the sachet line. Previously, operators manually carried out the production performance monitoring process using paper forms, and admins re-entered the data into the system. Although the monitoring process has begun to be carried out digitally using available tablets, its usage still needs improvement. Therefore, it is necessary to evaluate the user experience of the Production Performance Monitoring Information System to determine user satisfaction. The Honeycomb method is used in this study, which assesses seven aspects, namely accessible, credible, desirable, findable, usable, useful, and valuable. The results show the average final score of each aspect assessed, and the highest score of 66.45% is for the accessible and useful aspects. The study shows that the user experience evaluation of the Production Performance Monitoring Information System using the honeycomb method is generally good, but improvements are still needed in some aspects, such as accessibility and desirability.